(3GSGSjGJ GdebGQfI GdeQLYjI (B/s - (3WGdH, YdGA aQMGfs ((3YeGf(B: s (3OGQ UaGA(B, s, 2009)
(3GdOQGSGJ GdSGHbI Mhd GdebGQfI GdeQLYjI (B- (3JCWjQGJ fXQjI ddebGQfI GdeQLYjI (B-(3GdejRI GdJfGaSjI (B-(3YdGbI GdebGQfI GdeQLYjI HHYV GdEJLGgGJ GdEOGQjI GdMOjKI (B-(3ebGQfI CHYGO GdejRI GdJfGaSjI bHd hHYO JWHjb GdebGQfI GdeQLYjIs
(3HHdjhZQGajG(B: (3U(B.217-224s
Keywords: (3GOGQI GdGYeGds; (3GOGQI GdGfJGLs